Analisis Upaya Pengelolaan Sampah di Kecamatan Nanggalo Kota Padang - Dewantara, Bagus Putra; Syarief, Azhari (Lembaga Yasin AlSys, 2025)
The increasing amount of waste in urban areas, including in Nanggalo Sub-district, Padang City, poses a major challenge in its management. This study aims to analyze the distribution routes of waste collection vehicles and the capacity of temporary disposal sites (TPS) in the area. The research used a quantitative descriptive method with data collection techniques in the form of field observations, literature studies, and documentation. The analysis was conducted using GIS software for mapping waste distribution routes and calculating TPS capacity. The results showed that the routes of waste collection vehicles only cover the main roads, with the capacity of TPS in Nanggalo Sub-district being able to handle only 32% of the total daily waste generation of 30.01 tons. The low waste management carrying capacity index (0.32) reflects the poor waste management in this area. Therefore, additional polling stations, expansion of waste transportation routes, and community education are needed to support better waste management in accordance with Padang City Regional Regulation No. 21/2012.